2016
DOI: 10.1007/s13361-016-1405-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Cysteine Content in Proteins Utilizing Cysteine Selenylation with 266 nm Ultraviolet Photodissociation (UVPD)

Abstract: Abstract. Characterization of the cysteine content of proteins is a key aspect of proteomics. By defining both the total number of cysteines and their bound/ unbound state, the number of candidate proteins considered in database searches is significantly constrained. Herein we present a methodology that utilizes 266 nm UVPD to count the number of free and bound cysteines in intact proteins. In order to attain this goal, proteins were derivatized with N-(phenylseleno)phthalimide (NPSP) to install a selectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The value of bond-selective dissociation was demonstrated previously for a simple protein in disulfide mapping experiments at 266 nm, which produces a set of doublets for each precursor ion. 33 Paek and coworkers have also demonstrated that searching MS 2 spectra for conserved fragmentation patterns drastically reduces the number of crosslinked candidates. 41…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of bond-selective dissociation was demonstrated previously for a simple protein in disulfide mapping experiments at 266 nm, which produces a set of doublets for each precursor ion. 33 Paek and coworkers have also demonstrated that searching MS 2 spectra for conserved fragmentation patterns drastically reduces the number of crosslinked candidates. 41…”
Section: Resultsmentioning
confidence: 99%
“…Homolytic dissociation of the S-Se bond allows for analysis of free cysteine content. 33 These methods are convenient and facilitate simple analysis, but generally do not afford sequence information since the peptide backbone does not readily absorb 266 nm photons. 213 nm UVPD offers a unique compromise between the selectivity of 266 nm and the extensive dissociation observed at 193 nm.…”
Section: Introductionmentioning
confidence: 99%
“…16 Selenylation is mostly used to derivatize and protect the cysteine thiol group from oxidation, in vitro. 17 This variety of cysteine functions and their possible implication on a wide range of biological functions, make the cysteine residue an important target for function prediction in a given protein (Figure 1). Amino acid function prediction became increasingly important with the advent of the structure genomics consortium, 18 where a large number of protein crystal structures were solved with unknown functions; 3970 such structures were reported on 25 September 2020 in PDB database.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 One group of compounds that has been highlighted in the scientific community, both in the synthesis and the development of new therapeutic agents, is composed of organoselenium compounds. These compounds are obtained from reactions with elemental selenium 12 and electrophilic 13,14 Considering the potential of organoselenium compounds in the synthesis of new pharmaceutical drug candidates, a series of nine selenoglycolicamides were planned for evaluating an in silico study as new structures of drug candidates, obeying the Lipinski's rules. The compounds were synthesized using our selenoglycolic acid synthesis protocol, and these are the early studies of microbiological activity against bacteria (Staphylococcus aureus) and fungi (Candida albicans and Candida tropicalis).…”
Section: Introductionmentioning
confidence: 99%